Peripheral line dead space: an unrecognised phenomenon?. Issue 8 (25th July 2007) - Geggie, Dave; Moore, Deborah
Abstract : Objective: To determine if peripheral intravenous cannula dead space is taken into account when setting up intravenous infusions (in particular nitrate infusions) in the emergency department. Method: A postal survey of UK emergency departments. Results: Of the 143 (58%) of UK departments who responded, only 15% reported priming the cannula before commencing the nitrate infusion. Conclusions: Knowledge of peripheral intravenous cannula dead space in UK emergency departments is very poor and, as a result, there is probably significant widespread under treatment of patients in severe cardiogenic pulmonary oedema. Departments should amend their treatment guidelines to take account of peripheral cannula dead space